Bekasi City Government Policy In Financing Stunting In Children - Hanifa Muslimah, Rifa’at; Subhandi Bakhtiar, Handar (Jurnal KESANS : Kesehatan dan Sains, 2021)
Currently, nutritional problems in Indonesia are still in the spotlight, one of which is the problem of stunting in toddlers. The government shows its commitment to tackling stunting by making regulations regarding the acceleration of stunting reduction as stated in Presidential Regulation No. 72 of 2021. The health financing system is an effort to fund the health sector to support the implementation of health with the aim of achieving the highest health status. This study aims to provide an overview of the Bekasi City government's policy in financing stunting prevention in Bekasi City. The research method used is normative juridical, with a statutory approach. The policies issued by the Bekasi City Government regarding the Prevention and Control of Stunting are contained in the Bekasi Mayor's Instruction No: 440/1914/Bappeda and the establishment of the Task Force for the Acceleration of Stunting Prevention and Control is contained in Decree Number: 440/Kep.277-Bappelitbangda/V/ 2020. The results of this study show that the participation of the Bekasi City government has been very good from issuing policies related to stunting reduction efforts, forming and implementing 8 integration actions by involving multi-sectoral roles in government which is an effort to prevent stunting. The financing used in the stunting prevention process is funded by the Bekasi City Government from the Regional Revenue and Expenditure Budget (APBD) and or other funds that can be utilized by the relevant government sector to be in charge of 8 integration actions.